EVALUATING AND QUANTIFYING THE BIOACTIVE POTENTIAL OF HYGROPHILA SPINOSA - SMRUTI S. GAIKWAD; LATA P KOTHAPALLI; ASHA B THOMAS (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The quantification of Quercetin (QR) and Lupeol (LU) in the seed extract of Hygrophila spinosa has been accomplished using a highly efficient, rapid, and precise high-performance thin-layer chromatographic (HPTLC) method. Methods: This advanced technique employed a carefully optimized mobile phase consisting of toluene, ethyl acetate, methanol, and formic acid in a precise ratio of 5:4:2:0.5 (v/v/v/v) to meticulously elute the QR and LU markers from the extract on silica gel 60 F254 HPTLC plates, measuring 10×10 cm. Detection was conducted at a wavelength of 236 nm, ensuring accurate identification of the compounds. Results: Results revealed that the hydroalcoholic extract of H. spinosa contains substantial quantities of QR and LU, quantified at 17.0 mg/100 g and 17.4 mg/100 g, respectively. The robustness of the method has been thoroughly validated, demonstrating exceptional linearity, accuracy, precision, and specificity, as well as acceptable limits for both the limit of detection (LOD) and the limit of quantification. The calibration curve displayed remarkable linearity between 100 and 600 ng/band for both QR and LU, with a limit of quantitation of 4.97 ng/band for QR and 3.49 ng/band for LU, and LODs of 1.64 ng/band for QR and 1.15 ng/band for LU. Conclusion: This innovative method represents a significant advancement in the quantification of valuable bioactive compounds. It can be confidently applied to measure QR and LU levels in H. spinosa seed extracts and related formulations, thereby contributing to the advancement of research and applications in phytochemistry and natural product development.